“Nothing about us without us”: the Specialized Educational Care in the high school based on the perception of students of Special Education (Research, Society and Development, 2020)
The present study aims to analyze the perception students of special education, enrolled in a high school, about the specialized educational care and its articulation with the common classroom regarding its process of school inclusion. To this end, an exploratory-qualitative study was conducted in a state public high school located in the city of Iguatu/CE that includes special education. The data were collected through the interview recorded in audio format with twelve students of this modality enrolled in the school, being the data analyzed by approximation of the speech analysis. The results indicate a weakening of the process of school inclusion of these students in the common school, where the pecialized educational care, sometimes, is put in substitution to the common education, which goes in the opposite direction to the established by the legislation.